Flow cytometry analysis of guided tissue regeneration-associated human periodontal cells - KURU, LEYLA (WILEY, 2001)
Background: Expanded polytetrafluoroethylene (ePTFE) barrier membranes have been widely used for guided tissue regeneration (GTR) of the human periodontal ligament (PL). However, the precise cellular and molecular events involved in the re-growth of the new tissue are still unclear. Methods: Retrieved membranes and the newly -regenerated soft tissue (RT) underlying the membranes were used to examine the cells associated with GTR compared with normal human PL and gingival cells. Flow cytometry (FCM) was used, for the first time, to analyze the spindle-shaped fibroblast-like cells which were adherent to these membranes and the cells which grew out of the RT. Results: The results showed that the membrane-associated (M) cells had the lowest rate of proliferation and appeared to be larger and more granular than the other types of cell. Moreover, both the M- and RT-derived cells were found to express higher levels of the extracellular matrix (ECM) proteins Collagen type I, fibronectin, tenascin, and decorin. In addition, evidence based on FCM profiles identified distinct sub-populations of GTR cells in which fibronectin expression was markedly up-regulated compared with normal PL cells and which also differed in size and granularity. Conclusions: The results of this study show that cells associated with GTR barrier membranes and with the underlying tissue appear to have distinct phenotypic and functional activities consistent with the production of new periodontal connective tissue and periodontal regeneration.
Keywords: membranes, artificial; membranes, barrier; guided tissue regeneration; polytetrafluoroethylene/therapeutic use; periodontal ligament; fibroblasts; flow cytometry/utilization; EXPANDED POLYTETRAFLUOROETHYLENE MEMBRANES; CONTROLLED CLINICAL-TRIAL; HUMAN INTRABONY DEFECTS; FIBROBLAST SUBPOPULATIONS; BARRIER MEMBRANES; LIGAMENT CELLS; EXPRESSION; GINGIVAL; BONE; HETEROGENEITY